Relationship between the kinematical parameters in the propulsive phase and the sprint performance in front crawl swimming - Ichikawa, H.; Shiraki, T.; Nomura, T. (1st International Scientific Conference of Aquatic Space Activities, 2008)
The purpose of this study was to investigate the relationship between the kinematical parameters and the sprint ability in front crawl swimming. The subjects were nine well-trained male swimmers. They performed front crawl swimming with five different velocities (1.1-1.9 m/s) in swimming flume. The hand trajectory was obtained by three dimensional motion analysis. The propulsive phase was defined as the duration to push water backward. It was observed that there was a significant correlation between the relative propulsive duration in the trial 1.7 m/s and the best record of 50 m freestyle (r = -0.67, p < .05). The relative propulsive duration would have a possibility to be one of the parameters to evaluate the sprint ability in front crawl swimming, although it was difficult to discuss the swimming propulsion using only the kinematical parameter